Militarização das polícias e doutrina de segurança nacional no contexto do combate ao inimigo interno no Brasil (1967-1970) - Fernandes, Luís Eduardo Viana (Universidade Federal Rural do Semi-Árido, 2018)
This paper proposes to return to the dictatorship to analyze the influence of the National Security Doctrine in the militarization of the Brazilian police between 1967-1970, discussing the development of the intern enemy perspective to be combated in the revolutionary war context. For that, this research will to be developed by the deductive method, with the hypothesis that the military character of the police was crucial for them to have acquired the exclusivity of ostensive policing during the exceptional period, which also demands a dialectical reasoning directing the historical and legal investigation which will be done looking about direct and indirect sources by bibliographic and documental research and fixing as a model of institution the Public Force of the State of São Paulo. So, we will see the nuances of the institutional changes in the military police provided by the legal provisions at the federal level and by the inter security planning and guidelines of the military regime. That such measures caused a repressive structure whose traces are still in our democratic constitutional order. Therefore, as the demilitarization of the Brazilian police is a recurring issue on the discussion about public security, researching the context of its militarization with the primary purpose of acting in the repression of subversion in the dictatorship, allows us to insert the problem of the military police in the field of reform of the institutions, reinforcing the thesis of the need for demilitarization as a necessary measure for an effective Transitional Justice.
Monografia
Keywords: Polícia militar; Justiça de transição; Doutrina de segurança nacional; Military police; Transitional justice; National security doctrine; CIENCIAS SOCIAIS APLICADAS::DIREITO